Penerapan Pembelajaran Model Tutorial Berbasis Komputer Untuk Meningkatkan Hasil Belajar Peserta Didik: Application of Computer-Based Tutorial Model Learning to Improve Student Learning Outcomes - Elyn Ledia Salulur; Chandra Anugrah Putra; Muhammad Andi Setiawan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The research aims to determine student learning outcomes by implementing computer-based tutorial model learning.The research method used in this research is classroom action research (PTK). The data sources in this research are school principals, ICT subject teachers and students. The data collection techniques used are Planning, Implementation, Observation, Reflection and Documentation. Analysis of research data uses stages consisting of collecting lesson plans, questions and results from pre-test and post-test, and drawing conclusions and verification.The results of the research show that the factors that influence the increase in student results are: (1) The learning activities of students when learning ICT using a computer-based tutorial model have achieved the predetermined indicators of success and show that students are quite active during learning. (2) There is an increase in student learning outcomes when learning tik using a computer-based tutorial model. The test results and data obtained in the Preliminary Test (Pre-Action) obtained an average score of 54.28% below the KKM ≤70 with a classical score of 21.42%. Meanwhile, in Cycle I, student learning outcomes obtained an average score of 60.35 with classical completeness of 71.42%. This has achieved the researchers' predetermined success indicators, namely student learning outcomes with a KKM of 70 and classical completeness of 85%.